PERILAKU DAN KETERTARIKAN MASYARAKAT TERHADAP PENGGUNAAN JASA EVENT ORGANIZER - Aliviana Azhaar Rustianto; Paulina Tjandrawibawa (Universitas Ciputra Surabaya, 2020)
The purpose of this research is to clarify people behaviour and their enthusiasm towards event organiser service. Researcher will be using both quantitative and qualitative for the research methods. Which, researcher will distribute 114 survey inquiries as the quantitative method and interviewing clients as the qualitative method. The survey inquiries will be used by the researcher to discover people’s enthusiasm towards event organiser service. The survey result will be the first step for the researcher to confirm, what is event organiser in people’s perspective and what makes people feel enthusiastic when they are using event organiser service. The hypothesis of this research is people that feel enthusiastic towards the usage of event organiser service. Keyword : People Behaviour, People Enthusiasm, Event Organiser